Outsourcing motives, location choice and labour market implications: an empirical analysis for European countries - Marcus Neureiter; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2009)
We use data on motives of international outsourcing and location choices from a recent survey of European companies to assess the labour market repercussions at home. Employing Tobit models we differentiate between job losses as well as job creation for high and low skilled employees at the sector level in ten European home countries. Our findings are in conflict with public concerns about adverse employment effects resulting primarily from cost-oriented sourcing in low wage locations. The quantitative impact on job losses remains modest in the case of cost-saving motives. The simple divide between low and high wage locations hides substantial heterogeneity within both groups. We also find that job losses are typically compensated partly by new job creation, particularly for high skilled workers.
Keywords: F23; J21; 330; Outsourcing; outward FDI; motives; location choice; job loss; job creation; (un)skilled labour; Multinationales Unternehmen; Outsourcing; Auslandsproduktion; Direktinvestition; Standortwahl; Beschäftigungseffekt; Qualifikation; Ungelernte Arbeitskräfte; EU-Staaten